2018
DOI: 10.1097/mlr.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Type and Access to Health Care Providers and Appointments Under the Affordable Care Act

Abstract: Despite ACA-related gains in insurance coverage, those with on-exchange and off-exchange individual private insurance plans and Medicaid encounter more barriers to care than those with employer-based insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…Controlling for location of usual source of health care did not impact this relationship. The disadvantage experienced by those with Medicaid and Medicare coverage may stem from a variety of factors, including having a harder time getting an appointment, 28 narrower provider networks, different services covered, longer patient wait- times, cost-sharing between patient and insurance, and receiving poorer service from health care providers and their staff based on the insurance they utilize. Thus, both interpersonal and structural factors may be at play.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Controlling for location of usual source of health care did not impact this relationship. The disadvantage experienced by those with Medicaid and Medicare coverage may stem from a variety of factors, including having a harder time getting an appointment, 28 narrower provider networks, different services covered, longer patient wait- times, cost-sharing between patient and insurance, and receiving poorer service from health care providers and their staff based on the insurance they utilize. Thus, both interpersonal and structural factors may be at play.…”
Section: Discussionmentioning
confidence: 99%
“…While employer-sponsored coverage is a type of private insurance, we separate it from privately purchased coverage obtained through the individual market, because different categories of private insurance coverage have been shown to differentially impact access to health care. 28 Employersponsored coverage served as the reference category in analyses because this insurance type is associated with fewer barriers to health care and is the most common insurance type among Californians. 28 The second variable captured where the respondent went for their usual source of health care.…”
Section: Data Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…One recent study in California found that those with employer-based insurance had greater access to providers than those with either on-exchange and off-exchange individual private insurance plans or Medicaid [31]. Consistent with our psychiatry utilization ndings, this study found worse access to primary care among those with private coverage purchased on exchanges compared to private coverage purchased individually [31]. Another study found that patients often felt overwhelmed by the array of choices offered on the exchanges and were confused by terminology and websites [32].…”
Section: Discussionmentioning
confidence: 99%